2021
DOI: 10.1186/s13662-021-03371-3
|View full text |Cite
|
Sign up to set email alerts
|

Analytic and numerical solutions of discrete Bagley–Torvik equation

Abstract: In this research article, a discrete version of the fractional Bagley–Torvik equation is proposed: $$ \nabla _{h}^{2} u(t)+A{}^{C} \nabla _{h}^{\nu }u(t)+Bu(t)=f(t),\quad t>0, $$ ∇ h 2 u ( t ) + A C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In view [1], (10) and (11) are the discrete versions of the following versions of integration by parts. Definition 4 (integration by parts).…”
Section: The Delta Fractional Sums and Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In view [1], (10) and (11) are the discrete versions of the following versions of integration by parts. Definition 4 (integration by parts).…”
Section: The Delta Fractional Sums and Differencesmentioning
confidence: 99%
“…Recently, Bastos et al developed the theory on h-sum and h-di erence operators in discrete fractional calculus. For more recent applications of fractional Laplace transform, one can refer [8][9][10][11]. ese concepts are very well applied in discrete fractional transforms in the field of fractional calculus [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional difference equations (FDEs) have become a hot research topic in the mathematical and physical sciences. It has been found that the role of FDEs is very important in treating and modeling nonlinear problems with applications in mathematical analysis and various branches of science, including diffusion, plasmas, dynamic systems, nonlinear optics, and many other areas (see [16][17][18][19][20][21]).…”
Section: Introductionmentioning
confidence: 99%